Principal Leadership, School Culture, and Teacher Performance: The Mediating Role of Achievement Motivation in Private Schools in Jepara - Nazifah, Umi Ainun (Journal of Blended and Technical Education, 2026)
Objective: This study aims to analyze the influence of school principal leadership and school culture on teacher performance, with achievement motivation as a mediating variable, in private schools in Jepara Regency. Research Design & Methods: This study employs a quantitative approach with an exploratory research design. The population consisted of 9,003 teachers from private schools in Jepara Regency. Using the Slovin formula with a 5% margin of error, a sample of 383 teachers was obtained. Data were collected through a structured questionnaire and analyzed using Structural Equation Modeling (SEM) to test the direct and indirect relationships among the variables. Findings: The results indicate that school culture and principal leadership have a positive and significant influence on teacher performance. Both variables also significantly influence achievement motivation. Furthermore, achievement motivation has the strongest influence on teacher performance and significantly mediates the relationship between principal leadership, school culture, and teacher performance. However, the moderating effects tested in this study were not significant. Contributions:  This study contributes to the development of the educational management literature by providing empirical evidence on the integrative role of organizational and psychological factors in enhancing teacher performance, particularly in the context of private schools. Novelty: The novelty of this research lies in the integration of principal leadership and school culture with achievement motivation as mediating variables in a comprehensive analytical model, as well as its empirical focus on private schools in Jepara Regency, an area that remains under-explored